Phytochemical screening of Syzygium cumini (L.) extracts in different solvents - Hasanuzzaman, M; Islam, W; Islam, MB (Journal of Bio-Science, 2018)
Phytochemical screening of the secondary metabolites was performed with acetone, chloroform, methanol and n-hexane extracts of the leaves, roots, stem bark and seeds of the plant Syzygium cumini (Linn.) and were detected using various tests for identifying the isolated components. Acetone extract of the leaves showed the presence glycosides, phenols, proteins, resins and saponins while the stem bark extract showed the presence of alkaloids, flavonoids, glycosides, phenols, proteins, resins and saponins. All the above constituents except saponins were detected in the root extract. The seed extract contains alkaloids, carbohydrates, phenols, proteins and tannins. Chloroform extract of the leaves showed the presence of alkaloids, proteins and steroids while root extract contains alkaloids and steroids and that of seed extract alkaloids, carbohydrates, phenols, proteins and tannins, however, alkaloids and tannins were found in the stem bark extract. Methanol extract of the leaves and stem bark showed the presence of alkaloids, carbohydrates, flavonoids, glycosides, phenols, resins, saponins, steroids and tannins while the root extracts contain all the above constituents along with proteins. N-hexane extract of the leaves contain only alkaloids, roots contain alkaloids and resins and that of seeds contain carbohydrates and proteins while alkaloids, proteins and tannins were found in stem bark extract. The present findings reveal the presence of various medicinally important phytochemicals from the plant S. cumini extracts may have application in traditional system of medicine to cure various ailments J. bio-sci. 24: 11-18, 2016